Strategi Pengembangan Industri Kecil dan Menengah di Kabupaten Maluku Tengah - Marasabessy, Fitria Komalasari; Ramly, Fahrudin; Pattilouw, Djufri Rays (Public Policy, 2024)
Small and Medium Industries (SMEs) are one of the business sektors that have an important role in the regional economy. However, in its development, SMEs have various potentials, weaknesses, opportunities and even threats so that they cannot develop optimally like other business sektors. This research aims to provide an analysis of its development strategy. The method used is the SWOT method and Analysis Hierarchy Process (AHP) with the aim of identifying various potentials, weaknesses, opportunities and threats as well as priority development strategies in the future. The results of the SWOT analysis show that the strategy that needs to be used is a growth strategy by optimizing strengths to take advantage of emerging opportunities. Meanwhile, the results of the AHP analysis show that the priority policies in the growth strategy are policies in developing human resources.